Ionospheric tomography for the study of relative X‐ and O‐mode power over low‐ and mid‐latitude ionosphere. Issue 5 (11th March 2019) - Nandi, Sandip; Bandyopadhyay, Bijoy; Khatua, Soumen
Abstract : Realising the importance of the ionospheric effects on low Earth orbit (LEO) satellite signals, tomographic reconstruction method has been applied to study the relative X‐ and O‐mode power distribution at an altitude of LEO satellites over the low‐ and mid‐latitude regions of the Earth. Eight regions of the ionosphere in Northern and Southern Hemisphere have been reconstructed tomographically based on the Ionex TEC data and direct measurement TEC data over West Bengal, India and subsequently ray tracing of very high frequency waves has been performed. Then, based on the magnetoionic theory, the relative X‐mode power distribution has been investigated. Evaluation of the results and observations related to the existence of X‐mode only band and narrow O‐mode only band ensures the possibility of application of ionospheric tomography technique for study of relative absorption in the ionosphere. The outcome of this research will greatly assists the researchers to interpret the ionospheric effects on radio waves.